1981
DOI: 10.1177/014107688107400409
|View full text |Cite
|
Sign up to set email alerts
|

Are Patients Shocked by ECT?

Abstract: Summary: Seventy-two consecutive patients treated with electroconvulsive therapy (ECT) for severe mental illness were asked their opinions about ECT: 83% considered they had improved as a result of the treatment and 81% would have it again. Most found the experience neutral or pleasant and 54% thought the dentist more distressing. Claims in newspapers, magazines, television and elsewhere that ECT is cruel and frightening receive little support from the results of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(28 citation statements)
references
References 6 publications
(1 reference statement)
1
27
0
Order By: Relevance
“…As in some international studies, this study also found subjects' KAE adequate and satisfactory. Many subjects explained they got adequate information regarding ECT / they found it very beneficial and most of them have positive attitudes toward ECT 11,12,13 . Rates of benefit ranged from 50% to 100% (average 71%) 18, 19, 20, and 21. Subject in some studies (53% to 98%, average 70%) perceived ECT agreed its beneficial effects and willing to do ECT again if required 13,22,23,24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…As in some international studies, this study also found subjects' KAE adequate and satisfactory. Many subjects explained they got adequate information regarding ECT / they found it very beneficial and most of them have positive attitudes toward ECT 11,12,13 . Rates of benefit ranged from 50% to 100% (average 71%) 18, 19, 20, and 21. Subject in some studies (53% to 98%, average 70%) perceived ECT agreed its beneficial effects and willing to do ECT again if required 13,22,23,24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…[72] Hughes et al studied 72 patients submitted on ECT and reported that 83% of the total patients showed improvement. [73] Freeman and Kendell carried the same type of study on 166 patients and concluded that 57.2% find this ECT useful. [74] However, another study carried out by Malekian et al demonstrated that satisfaction with ECT was independent from treatment outcome.…”
Section: Electroconvulsive Therapymentioning
confidence: 96%
“…In Hughes et al's study, of the 72 patients who had been submitted to ECT, 83% have reported improvement with the treatment and 81% of them would do it again. 41 Two studies assessed the perception of patients who had been submitted to ECT in their adolescence 42 and that of their parents. 43 Of the 26 patients assessed, 50% have reported that ECT was a useful treatment, whereas 60.7% of the 28 parents evaluated reported benefit with the treatment.…”
Section: Ect and Remission Of Symptomsmentioning
confidence: 99%